Design, synthesis and structure–activity relationship of indoxacarb analogs as voltage-gated sodium channel blocker. Issue 20 (15th October 2015) - Hao, Wenbo; Fu, Chunling; Yu, Huijuan; Chen, Jian; Xu, Hanhong; Shao, Guang; Jiang, Dingxin
Graphical abstract